2021
DOI: 10.1007/s00414-021-02624-w
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Swiss autosomal marker set to 32 STRs

Abstract: By genotyping 1198 individuals with the Qiagen Investigator® HDplex Kit, we expand the Swiss autosomal STR dataset to 32 loci, providing additional resources for complex kinship cases. We present the first high-quality allele frequency dataset for loci D2S1360, D5S2500, D7S1517, and D10S2325 that will be accessible through the ENFSI reference database STRidER. For loci D3S1744, D4S2366, D6S474, D8S1132, and D21S2055, we provide a first European STRidER dataset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similarly, Ghana has the highest TPOX-9 and FGA-27 allele frequencies [56] and reports one of the lowest CVD-correlated death rates. On the other hand, Switzerland had the highest TH01-9.3 and vWA-18 allele frequencies, in concordance with the CVD-death rate [50,51,78,79]. It is important to emphasize that even though the studies by Meraz-Rios et al [36], Hui et al [33], and Courts et al [76] suggested a potential association between STRs and cardiovascular disease predisposition, none of the relationships mentioned in this review provide evidence of a direct causal relationship.…”
Section: Population Comparisonsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, Ghana has the highest TPOX-9 and FGA-27 allele frequencies [56] and reports one of the lowest CVD-correlated death rates. On the other hand, Switzerland had the highest TH01-9.3 and vWA-18 allele frequencies, in concordance with the CVD-death rate [50,51,78,79]. It is important to emphasize that even though the studies by Meraz-Rios et al [36], Hui et al [33], and Courts et al [76] suggested a potential association between STRs and cardiovascular disease predisposition, none of the relationships mentioned in this review provide evidence of a direct causal relationship.…”
Section: Population Comparisonsupporting
confidence: 53%
“…Individuals carrying the vWA-18 allele BioMed Research International showed a high risk of venous thromboembolism in the Mexican population [36]. Noteworthily, Switzerland has the highest vWA-18 (0.2049), and as stated before, CVD accounts for 35% of the total deaths in the country [50,51,78].…”
Section: Th01mentioning
confidence: 99%
“…[23][24][25] The Investigator HDplex Kit (Qiagen, Germany) has been studied in many populations to expand STR data. 8,[26][27][28][29] However, no study has been conducted with the kit in question for the Turkish population so far.…”
Section: Discussionmentioning
confidence: 99%